Racial Stacking Among Special Teams Units in American College Football - Coutts, Steven (Race and social problems, 2021)
Racial stacking refers to a form of racial discrimination structured within the organization of sports teams and franchises. It is a persistent and pervasive social problem. The concept, first introduced in the 1970s, documents the active process of selecting and assigning players to particular positions on the field of competition based on a players’ racial or ethnic background. The concept extends to the selection of positions of governance and oversight within sports organizations, such as coaches, managers, scouts, and front office staff. Although there has been a breadth of research on offensive and defensive positions of American football teams, no studies to date have examined Special Teams, a unit or collection of positions on a football team tasked with kicking (including field goals), punting and kick-off, and punt returns. The current study fills a gap in the literature and utilizes visual analysis of media guides and game film of all twelve football teams in the Pacific-12 intercollegiate athletic conference for three consecutive seasons (2016–2018), analyzing the racial demographics of all positions within these Special Team units. Findings from this study confirm the persistent presence of spatial centrality and racial stacking within Special Teams units of American college football, reproducing racial discrimination within college sports and American higher education today. Findings also contribute to a more nuanced understanding of figurative centrality within the racial stacking literature.